2016
DOI: 10.1016/j.ssresearch.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with two types of child custody loss among a sample of African American mothers: A novel approach

Abstract: African American families are overrepresented in the Child Welfare System; however, extant research on this phenomenon has (1) focused mostly on Caucasian or mixed-race samples and (2) has not examined informal custody arrangements alongside official child custody loss. This research addresses these gaps in the literature by examining factors associated with both official and informal child custody loss among a sample of African American mothers. Multinomial regression results show that having ever been incarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Recent studies of African American mothers in one U.S. state found that not only did substance use and criminal involvement increase the likelihood a mother would lose custody of her children (Harp and Oser 2016) but that maternal substance use and criminal involvement actually increased in the months after custody loss (Harp and Oser 2018). Thus, these punitive CWS policies have a negative effect on mothers struggling to cope with the loss of their children, and rather than decrease maternal drug use, may contribute to an increase in these behaviors, thus reducing a mother's chances of being rehabilitated and reunited with her children.…”
Section: Over-involvement In the Cws And Its Effectsmentioning
confidence: 99%
“…Recent studies of African American mothers in one U.S. state found that not only did substance use and criminal involvement increase the likelihood a mother would lose custody of her children (Harp and Oser 2016) but that maternal substance use and criminal involvement actually increased in the months after custody loss (Harp and Oser 2018). Thus, these punitive CWS policies have a negative effect on mothers struggling to cope with the loss of their children, and rather than decrease maternal drug use, may contribute to an increase in these behaviors, thus reducing a mother's chances of being rehabilitated and reunited with her children.…”
Section: Over-involvement In the Cws And Its Effectsmentioning
confidence: 99%
“…The prevalence of substance use among mothers who are involved in childcare proceedings is high and is related to negative child placement outcomes, such as lower rates of reunification, higher rates of out-of-home placement, greater risk of re-entry into the child welfare system and permanent loss of parental rights (Green et al, 2007;Taplin & Mattick, 2015;Tracy, 1994;Tsantefski et al, 2014). An estimated 50% to 80% of childcare proceeding cases across the world involved mothers with substance use problems (Harp & Oser, 2016;Public Health England, 2018;Taplin & Mattick, 2013) and approximately 50% of mothers in substance use treatment services have experienced the loss of the care of at least one of their children (Porowski et al, 2004;Tsantefski et al, 2014). However, the relationship between maternal substance use and child removal is not straightforward, with substance use rarely being the only contributor to the relationship (Wall-Wieler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…African American mothers with substance abuse problems engaging in crime are at significant risk for child custody loss, arrest, and incarceration (Harp & Oser, 2016; Henderson, 1998; Rockhill et al, 2008; Schilling et al, 2004; Sedlak & Schultz, 2004; Tracy, 1994; USDHHS, 1999). A recent study of African American mothers found that mothers incarcerated following a conviction had significantly higher odds of experiencing both informal and official custody loss (Harp & Oser, 2016). Furthermore, while having a childhood history of traumatic victimization increased the mothers’ odds for losing informal custody, it was homelessness, having more children, identifying as lesbian or bisexual, and using crack/cocaine that increased the odds of official custody loss (Harp & Oser, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of African American mothers found that mothers incarcerated following a conviction had significantly higher odds of experiencing both informal and official custody loss (Harp & Oser, 2016). Furthermore, while having a childhood history of traumatic victimization increased the mothers’ odds for losing informal custody, it was homelessness, having more children, identifying as lesbian or bisexual, and using crack/cocaine that increased the odds of official custody loss (Harp & Oser, 2016). Because substance use and criminality increase a parent’s likelihood of abusing and/or neglecting their children, they also predict a parent losing custody – while some of the other predictors are not as well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation